(untitled) - Enas Bahaj; Abdulquddus Mohammad (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The performance of an employee is influence by several factors, in which rewards seem to be the most important one. Thus, this study was conducted to examine the relationship between rewards and employee performance at Abdul Latif Jameel (ALJ) Company. This study was carried based on quantitative method. Random sampling method was used to select the sample. The sample populations of this work were 50 employees from the sales and service department. Data collection was done using survey questionnaire. The findings of this work have shown that 95% of the respondents have agreed that they feel pride in working for ALJ. The result shows that there are certain factors that do contribute to the relationship between rewarding employees and result in better performance of employees. Furthermore, the finding this study has shown that AJL Company needs to improve its organization policies in few areas such as development and career opportunities, good benefits, basic pay and incentives. This is needed to further enhance the work performance of its employees.